HUBUNGAN FLIPPED CLASSROOM DENGAN KEPUASAN DAN KECEMASAN BELAJAR ONLINE MAHASISWA JURUSAN TEKNIK INFORMATIKA DAN KOMPUTER, UNIVERSITAS NEGERI MAKASSAR - Rifqa Awalia; Nurikhlas Nurpa Gunawan; Della Fadhilatunisa; M Miftach Fakhri; Jumadil Ahmad Safii; Muh Akbar B (Sakura Digital Nusantara, 2023)
The new policy occurred in the world of education, where before the Covid-19 outbreak learning that required learning in the classroom or building, in this case, face-to-face learning turned into online learning. One of the innovations in learning methods that emerged when online learning was established was the Flipped Classroom learning model. This research aims to determine the relationship between the Flipped Classroom learning model and the satisfaction and anxiety of online learning for students in the Informatics and Computer Engineering department, Makassar State University. This research was conducted by applying descriptive research methods with a quantitative approach. The population in this study was 42 students. The resulting data comes from data collection in the form of questionnaires that are disseminated online using google form. Data analysis using a Likert scale consisting of 4 alternative answer choices. Based on the results of this study, it can be concluded that there is a relationship between Flipped Classroom and the satisfaction and anxiety of online learning for students majoring in Informatics and Computer Engineering, Makassar State University.